Performance of pigs fed corn, sorghum, or wheat with 0 or 4% added fat - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1978)
We used 96 crossbred pigs averaging 8.3 kg (19.3 lbs.) to compare performances with sorghum, corn, or wheat with 0 or 4% added fat (tallow). The trial ended when pigs averaged approximately 220 pounds. Grain source (sorghum, corn, or wheat) did not affect average daily gain or feed efficiency of pigs during any ration phase (starter, grower, or finisher). Adding fat (to each grain ration) reduced feed intake and improved feed efficiency during each ration phase. The greatest improvement in feed efficiency from added fat was during the finishing phase.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Performance; Corn; Sorghum; Wheat